Akad dan Peranannya Dalam Transaksi - Muh. Yusril; Muspita Sari (Universitas Teknologi Surabaya, 2024)
Akad is a statement of intention and will of both parties or more for a muamalah activity such as buying and selling, leasing, representation or pawn with the aim of establishing the pleasure of both parties and causing legal consequences on the object of the contract. An agreement is defined as an agreement between two or more parties involving the exchange of property or services, and in which the parties mutually agree on certain terms. Akad can include various types of agreements, ranging from buying and selling, loans, leases, to business cooperation. Akad can also be in the form of a transaction or agreement between someone (who submits) and another person (who receives) for the implementation of an act, such as a sale and purchase contract, a lease contract, and a marriage contract